Desaign DESIGN OF BOOKKEEPING IMPLEMENTATION STRATEGY IN UMKM USING SIMPLE FINANCIAL AND TAX SYSTEM USING EXCEL IN Y.F SAUDARA RESTAURANT - Mardianasari, Lili; Iqbal, Johandri; Yuliansyah, Dwi Novrian (Journal of Applied Accounting And Business, 2026)
Micro, Small, and Medium Enterprises (MSMEs) often face difficulties in implementing structured bookkeeping and financial reporting in accordance with accounting standards. Rumah Makan Y.F Saudara still applied manual financial recording, resulting in difficulties in determining profit and tax obligations. This study aims to design and implement a simple bookkeeping and taxation system based on Microsoft Excel in accordance with the Financial Accounting Standards for MSMEs (SAK EMKM). This research uses a qualitative approach with data collection through observation, interviews, and documentation. The designed system includes cash transactions, purchases, sales, income statements, notes to financial statements, and MSME final income tax calculation. The results show that Microsoft Excel improves accuracy, organization, and ease of financial management and helps MSMEs understand their financial condition and tax responsibilities.